Implementation of an emergency department virtual follow-up care process in a community-based hospital: a quality improvement initiative. Issue 2 (11th April 2022) - El-Zammar, Diala; Johal, Raj; Eng, Janice; Schulz, Tiffany
Abstract : During the COVID-19 pandemic, patients were apprehensive to seek acute care resulting in delayed diagnoses of serious conditions and reduction in emergency room (ER) visits by 50% in the Fraser Health Authority. Patients who did present to the ER left prior to their results being available and some refused admission and critical treatments. At the Chilliwack General Hospital ER, a virtual care clinic was established to follow-up on patients after their initial ER visit, providing test results and ensuring patients are not clinically deteriorating at home. Specific criteria were created for safe referral to virtual follow-up. For 2 hours daily, an ER physician contacts selected patients by telephone to provide a virtual follow-up based on the patients' needs. Through the emergency department virtual care (EVC) pilot project, from May 14 to August 31, 2020, on average 58 telehealth visits were conducted weekly, with 19% of visits reaching unattached patients without a regular primary care provider. A patient survey revealed that 75% of respondents were very satisfied or satisfied with telephone virtual care as a follow-up to their emergency department (ED) visit, while 95% would like to continue to receive telephone follow-up care. Additionally, based on a physician survey, 80% of providers were satisfied or very satisfied with the overall EVC experience. The majority (80%) would like to continue to provide the service. One patient was referred for a virtual care follow-up for imaging results that did not meet the referral criteria; the patient was diagnosed with a perforated appendicitis. They had an atypical presentation of abdominal pain and their care was delayed by several hours than if they were to present to the ED for in-person follow-up. The process and referral criteria may require minor modification and must be followed strictly to ensure safety and efficiency in providing telehealth follow-up in the acute care setting.